(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Efficient micro-propagation of mulberry (Morus indica L.) plays a crucial rolefor its agricultural and commercial applications. This study focuses on optimizing in vitro micro-propagation including rooting using nodal explantson MS basal medium, evaluating the effects of phyto-hormones e.g. BAP (6-Benzylaminopurine) and NAA (⍺-Naphthalene acetic acid) concentrations on shoot and root development. Various concentrations of BAP (0.5-3.0 mg/l) were tested for shoot initiation, in addition with 0.3 mg/l NAA kept constant for shoot development. Rooting was assessed using NAA concentrations ranging from 0.5 to 3.0 mg/l. The highest mean number of shoots (6.75 shoots/ explants) was achieved at 8.0 mg/l BAP, while 2.5 mg/l NAA resulted in the highest rooting percentage (85%) and root length (4.50 cm). Significant effects of BAP and NAA on shoot elongation, leaf production and rooting characteristics were observed. This study demonstrates that optimizing BAP and NAA concentrations significantly enhances the in vitro regeneration of mulberry, providing a reliable method for clonal propagation. These findings hold potential for commercial propagation and breeding programs for the improvement of mulberry. Plant Tissue Cult. & Biotech. 35(1): 13-20, 2025 (June)